Design and economic viability of a hybrid solar/gas pasteurization system for developing countries - Oumaima Guizani; Nabiha Naili; Bourhan Tashtoush; Sami Kooli (Case Studies in Thermal Engineering)
This work aims at developing a hybrid solar/gas pasteurization system by integrating a regenerator that utilizes high-temperature short-time (HTST) pasteurization techniques. Solar pasteurization facilitates localized milk processing, thereby reducing milk loss during transit. This system consists of a solar heating loop, a pasteurization loop, and a solar cooling loop utilizing an absorption chiller (heat pump). An extensive experimental study is conducted to assess the energy and exergy efficiency of system. A parametric analysis and numerical model utilizing TRNSYS software are conducted to determine the dimensions of the solar heating and cooling loops, as well as to evaluate heat transfer within the pasteurizer and the energy performance. An economic analysis is conducted to enhance the profitability of the hybrid solar/gas pasteurization system. The findings indicate that the regeneration rate for heating and cooling is 76 %. The heat loss in the pasteurizer is approximated at 2 % of the total energy utilized for heating or cooling. The actual specific heat requirement for milk pasteurization is estimated at 53 kJ/kg. Concentrating parabolic and evacuated tubes yield optimal efficiency with collector fields of 36 m2 and 25 m2, respectively. The payback period for the solar cooling system is approximately 6.3 years, while that for the electric compressor chiller is about 2 years. The results indicate that the hybrid solar/gas pasteurization system is both feasible and economically viable.